How do traditional donors respond when beneficiary countries set up their own aid agencies? : case studies of India, Brazil and South Africa - Teichmann, Christina (Department of Political Studies, 2016)
Emerging donors, such as India, Brazil and South Africa, have provided assistance to other developing countries for many decades. However, the creation of dedicated aid agencies in emerging donor countries is a relatively new feature. The establishment of these aid agencies is often motivated by the objective of better coordinating and managing the increasing volume and scope of their development assistance activities. Since many of these emerging donors are also recipients of Official Development Assistance (ODA) from traditional donors, this institutionalization and professionalization of their development assistance raises some difficult questions. How do traditional donors perceive this new development in beneficiary countries and how do they respond to it in terms of aid allocations and co-operation arrangements? Do traditional donors still perceive beneficiary countries that are in a position to provide development assistance to other countries as being eligible to receive aid? These are the fundamental questions that this research study aims to answer. This research study is based on the hypothesis that the creation of dedicated aid agencies in beneficiary countries prompts traditional donors to either freeze, reduce or terminate ODA and rethink their development cooperation strategies. It argues that traditional donors perceive beneficiary countries with dedicated aid agencies as no longer in need of foreign assistance. In order to test this hypothesis and identify changes in the flow of aid, the research study compares official aid flow data for five selected traditional donors (France, Germany, the UK, the US and EU Institutions) to three emerging donor countries (India, Brazil and South Africa) before and after the establishment of dedicated aid agencies. The research further investigates whether other factors, such as beneficiary countries' socioeconomic performance and compliance with DAC norms and standards, play a role in traditional donors' aid allocation decisions. Alongside the quantitative analysis, the research uses semi-structured elite interviews with representatives of the five traditional donors as well as development cooperation experts to solicit qualitative responses. The findings of the quantitative and qualitative analysis suggest that the establishment of dedicated aid agencies in emerging donor countries does not have a negative impact on traditional donors' aid allocations. Other factors, such as the economic status of beneficiary countries, domestic debates and the strategic interests of traditional donors', seem to play a much more important role in this regard. In fact, traditional donors welcome the creation of such aid agencies and actively support beneficiary countries in this endeavour. Traditional donors expect that such aid agencies will promote transparency and accountability and increase the effectiveness of aid.